Geospatial Development Using GIS Smart Planning - Ana Cornelia BADEA; Gheorghe BADEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2019)
Zoning is the most effective public tool for controlling land use, reflecting the spatial separation of urban land use incompatibilities and influencing, consequently, the physical economic and social structure of cities. In this paper we want to emphasize the possibilities and benefits of using dedicated GIS solutions for geospatial planning, integrating 3D and 2D data. At present, GIS provides complex tools dedicated to spatial planning analyzes, of which we chose a new Esri solution. The results consist of setting up the appropriate planning parameters, correlated with the local urban planning regulation and applying a coherent workflow in ArcGIS Urban for the GIS analysis of the reconfiguration of an area in Bucharest, as example. We have demonstrated the advantages of using intelligent spatial planning products to verify the conditions provided in the local urban planning regulations. We highlighted the possibility to highlight by analyzing certain evolving indicators, such as population, degree of employability, etc. Obviously, as more relevant Romanian statistical data will be available in the online environment, such analyzes may increase as complexity level.